Precision pulse capsulotomy: performance metrics and utility in routine and complex cases. Issue 11 (November 2020) - Ifantides, Cristos; Lee, Junhun; Rouweyha, Rajy; Vital, Mark; Sretavan, David
Abstract : Surgeons in diverse practices reported good capsulotomy performance using PPC in their first 50 to 150 cases. PPC capsulotomy exhibited utility in both routine and challenging clinical scenarios. Abstract : Purpose: To evaluate precision pulse capsulotomy (PPC) performance. Setting: University and private practice in the United States and South Korea. Design: Multicenter retrospective analysis. Methods: The surgical videos of 337 cataract surgeries with PPC capsulotomy performed by 4 surgeons at 4 centers were used to assess capsulotomy outcomes including completion rate, diameter, roundness (ovality), and quality of capsular overlap. Results: PPC use resulted in 99.4% free-floating capsulotomies from 337 cases. Video image analysis in a subset (n = 52) yielded a mean capsulotomy diameter of 5.0 mm ± 0.16 mm SD (95% CI, 4.96-5.04 mm). Capsulotomies were round to slightly oval at the end of the case with a mean ovality of 3.0% ± 2.86% (95% CI, 2.22%-3.78%; 360 degrees capsular overlap was obtained in 98% of cases. The offset of the capsulotomy center with the intraocular lens (IOL) optic center was 197 μm ± 122 μm (SD) (95% CI, 148-246 μm). PPC was used successfully in traumatic cataracts with compromised anterior and posterior capsule, phacodonesis, intumescent cataract with constricted pupil, and zonular dialysis and in penetrating keratoplasty with open-sky extracapsular cataract extraction. Conclusions: Surgeons obtained good PPC capsulotomy outcomes in routine and challenging cases. Little variation was observed in achieving free-floating capsulotomies with approximately 5.0 mm diameter and complete capsular overlap. Variation was observed in the amount of offset between the capsulotomy center and the center of the IOL optic. PPC was useful in cases with multiple comorbidities that challenge capsulotomy performance.